Financial cryptography and data security : FC 2016, International Workshops BITCOIN, VOTING, and WAHC, Christ Church, Barbados, February 26, 2016, revised selected papers /: FC 2016, International Workshops BITCOIN, VOTING, and WAHC, Christ Church, Barbados, February 26, 2016, revised selected papers. (2016) - Unknown
No abstract available